2011
DOI: 10.1002/chem.201102404
|View full text |Cite
|
Sign up to set email alerts
|

Alkali‐Metal‐Ion Catalysis and Inhibition in the Nucleophilic Displacement Reaction of Y‐Substituted Phenyl Diphenylphosphinates and Diphenylphosphinothioates with Alkali‐Metal Ethoxides: Effect of Changing the Electrophilic Center from PO to PS

Abstract: A kinetic study of the nucleophilic substitution reaction of Y-substituted phenyl diphenylphosphinothioates 2 a-g with alkali-metal ethoxides (MOEt; M = Li, Na, K) in anhydrous ethanol at (25.0±0.1) °C is reported. Plots of pseudo-first-order rate constants (k(obsd)) versus [MOEt], the alkali ethoxide concentration, show distinct upward (KOEt) and downward (LiOEt) curvatures, respectively, pointing to the importance of ion-pairing phenomena and a differential reactivity of dissociated EtO(-) and ion-paired MOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 89 publications
(31 reference statements)
0
36
0
Order By: Relevance
“…In contrast, the plots of k obsd vs. [EtOK] for the reactions of substrates bearing a strong electron-withdrawing Figure 1 is typical for alkaline ethanolysis of esters in which alkali-metal ions behave as a Lewis acid catalyst. [8][9][10][11][12] Thus, one can suggest that K + ion catalyzes the reactions of 7a-i with EtOK, although the catalytic effect becomes insignificant for the reactions of substrates possessing a strong electron-withdrawing substituent in the benzoyl moiety (e.g., 7h and 7i).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the plots of k obsd vs. [EtOK] for the reactions of substrates bearing a strong electron-withdrawing Figure 1 is typical for alkaline ethanolysis of esters in which alkali-metal ions behave as a Lewis acid catalyst. [8][9][10][11][12] Thus, one can suggest that K + ion catalyzes the reactions of 7a-i with EtOK, although the catalytic effect becomes insignificant for the reactions of substrates possessing a strong electron-withdrawing substituent in the benzoyl moiety (e.g., 7h and 7i).…”
Section: Resultsmentioning
confidence: 99%
“…8 In contrast, we have shown that Li + ion inhibits the corresponding reaction of 4-nitrophenyl diphenylphosphinothioate (1b), while K + and 18-crown-ether (18C6) complex K + ions catalyze the reaction. 9 Similarly contrasting results have been reported for the reactions of 4-nitrophenyl diethyl phosphate (2a, paraoxon) and phosphorothioate (2b, parathion) with EtOM. 10 Thus, a cyclic transition state (i.e., TS I ) has been suggested to catalyze the reaction by increasing the electrophilicity of the reaction center on the basis of the contrasting M + ion effects found for the reactions of the P=O and P=S centered electrophiles.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…5a In contrast, we have shown that Li + ion inhibits the corresponding reaction of 4-nitrophenyl diphenylphosphinothioate (1b) while K + and 18C6-complexed K + ions catalyze the reaction. 8 A similar result has been reported for the reactions of 4-nitrophenyl diethyl phosphate (2a, paraoxon) and 4-nitrophenyl diethyl phosphorothioate (2b, parathion) with EtOM (M = Li, Na, K), e.g., M + ions catalyze the reactions of 2a in the order K + < Na + < Li + while the reaction of 2b is strongly inhibited by Li + ion but is catalyzed by K + and 18C6-complexed K + ions. 9 These demonstrate convincingly that the effect of M + ions is dependent on the nature of the electrophilic centers (e.g., P=O vs. P=S).…”
Section: -11mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Since Lewis acidity increases as the charge density increases, most studies have focused on reactions involving multivalent metal ions (e.g., Mg …”
Section: Introductionmentioning
confidence: 99%